RETRACTED: Mechanisms of M2 Macrophage-Derived Exosomal Long Non-coding RNA PVT1 in Regulating Th17 Cell Response in Experimental Autoimmune Encephalomyelitisa - Wu, Lei; Xia, Jinjin; Li, Donghui; Kang, Ying; Fang, Wei; Huang, Peng (Frontiers in Immunology, 2020)
Long non-coding RNA (lncRNA) is pivotal for multiple sclerosis (MS), but the potential mechanism of lncRNA PVT1 in MS animal model, experimental autoimmune encephalomyelitis (EAE) still remains unclear. In this study, macrophages were firstly isolated and induced to polarize into M2 macrophages. M2 macrophage-derived exosomes (M2-exos) were extracted and identified, and EAE mouse model was established and treated with M2-exos. The effect of M2-exos on EAE mice was evaluated by clinical scores. The proportion of Treg and Th17 cells in spinal cord cells and splenocytes, and levels of inflammatory factors were measured. The targeting relationships among PVT1, miR-21-5p and SOCS5 were verified. The expression of JAKs/STAT3 pathway-related proteins was measured. After M2-exos treatment, the clinical score of EAE mice decreased, and demyelination and inflammatory infiltration improved; Th17 cells decreased, Treg cells increased, and the levels of inflammatory factors decreased significantly. SOCS5 and PVT1 were downregulated and miR-21-5p was upregulated in EAE mice. PVT1 could sponge miR-21-5p to regulate SOCS5. SOCS5 alleviated EAE symptoms by repressing the JAKs/STAT3 pathway. Together, M2-exos-carried lncRNA PVT1 sponged miR-21-5p to upregulate SOCS5 and inactivate the JAKs/STAT3 pathway, thus reducing inflammation and protecting EAE mice. This study may offer novel treatments for MS.